Respuesta :
Answer:
Step-by-step explanation:
2x + 5y = 14 -------------(i)
x + 3y = 16 ----------------(ii)
To eliminate x, multiply the second equation by (-2)
(ii)*(-2) -2x - 6y = -32
(i) 2x + 5y = 14 { Now add & x is eliminated}
- y = - 18 {divide by (-1)}
y = 18
Plug in y =18 in Equation (i)
2x + 5*18 = 14
2x + 90 = 14
2x = 14 - 90
2x = -76
x = -76/2
x = -38
Answer:
Step-by-step explanation:
hello :
2x + 5y = 14...(*)
x + 3y = 16....(**)
multiply (**) by -2 : -2x-6y=-32 ...(***)
add(*) and (***) : -y=-18 so y = 18
put this value in to (*) : 2x+5(18)=14
2x = -76
x = - 38